Perception, Beliefs, and Causal Attribution of Autism Early Signs in Ecuadorian General Population - Buffle, Paulina; Gentaz, Edouard; Vivanti, Giacomo (Frontiers in Psychology, 2022)
The identification and diagnosis of children with autism currently rely on behavioral presentation and developmental history. Cultural norms and other socio-demographic factors can influence what is expected or non-expected behaviors in a developing child. Perceptions, beliefs, and causal attribution of early signs can influence families' help-search behaviors. Lack of recognition of autism's first manifestations can critically delay the age of diagnosis, the provision of informed guidance to families, and the implementation of adapted interventions during the critical period of early development. Furthermore, a lack of understanding of early signs as the manifestations of a developmental condition may increase stigma and non-conventional explanations. Still, cultural and socio-demographic factors are largely understudied, particularly in low-and middle-income settings. Based on the hypothesis that non-specialists such as family members and friends are one of the first sources of referral in Latin American contexts, we aimed to study the general population's perceptions and the explanatory causes of autism's early signs. One-hundred-and-eighty-three Ecuadorian adults responded to a questionnaire developed for this study, describing sixteen ASD-related behaviors. Results indicated that, with the exemption of language impairment and self-injurious behaviors, a substantial proportion of participants did not endorse many behaviors as concerning. Also, language impairment was the only behavior identified as related to a developmental disorder. Additionally, most participants attributed the majority of behaviors listed in the questionnaire to causes unrelated to ASD, such as child personality. We discuss the impact of those findings in clinical practice and on awareness programs.